Social Health Security Program in Nepal: Opportunities and Challenges - Panday, Ruku (Nepalese Journal of Insurance and Social Security, 2019)
The study aims to assess the opportunities and challenges of the health insurance program carried out by Health Insurance Board as a social insurance program by Government of Nepal. Data have been collected through in-depth interview with 21 persons including the social health insurance policyholders, and non-policyholders who are inhabitants of Rantanagar Municipality- 6, and Bharatapur Metropolitan City- 10 of Chitwan district. Besides, experts in insurance and senior managers of insurance companies were also interviewed. It has followed the interpretive-naturalistic approach with the method of interviewing. As per the opinion of respondents HIP is effective in cost reduction of rich, and access to health service for poor. In government hospitals policyholders suffer from prolonging waiting, lack of facilities and experts and in private hospitals there is undue expenditure and discrimination in expert service. Even though the objective of the social health program is established social justice, cash-payer and insurance-payers are discriminated; corroborating the nature of neoliberal society. There are still uninsured persons because of ignorance, lack of premium, and distrust of HI service. The study suggests that HI service should be delivered through non-profit hospitals, the highest quality without discrimination of cashpayer and insurance-payer, and prolonged waiting.